Assessment of COVID-19 Vaccine Coverage and Acceptance Determinants in Western Libya - Ibtesam Amer; Zakaria Bannur; Jenan Jalal; Saja Ben Othman; Esra Abuaisha; Aseel Khaleefah; Rayan Altayib; Nuriddin Ahmed (AlQalam Journal of Medical and Applied Sciences, 2025)
COVID-19 vaccination is crucial to controlling the pandemic, yet disparities in uptake exist globally. Libya, affected by political instability and fragile healthcare systems, presents unique challenges in vaccine coverage. This study aimed to assess COVID-19 vaccination coverage and identify the factors influencing vaccine acceptance in certain areas of western Libya, namely Zawiya, Sabratha, and Sorman. A cross-sectional study was conducted between January and June 2024, enrolling 400 adult participants through stratified random sampling. Data were collected using a structured questionnaire covering sociodemographic characteristics, vaccination status, awareness, and attitudes toward COVID-19 vaccination. Statistical analysis included descriptive statistics, chi-square tests, and logistic regression (SPSS v26). Vaccination coverage was 56.3% overall, with slight variation between cities (Zawiya 58.5%, Sabratha 55.5%, Sorman 54.6%). The primary reasons for vaccination were personal health protection (64%) and protecting family members (52%). Hesitancy was mainly due to fear of side effects (49%), mistrust in effectiveness (38%), and misinformation (32%). Significant predictors of vaccine uptake included higher education (AOR = 2.31), presence of chronic disease (AOR = 1.89), good awareness (AOR = 2.75), and trust in health authorities (AOR = 2.08). COVID-19 vaccination coverage in western Libya is moderate, with significant barriers including hesitancy and access challenges. Targeted public health interventions focusing on education, risk communication, and improved vaccine accessibility are essential to enhance uptake and protect population health.